2012
DOI: 10.1097/aln.0b013e31825ae693
|View full text |Cite
|
Sign up to set email alerts
|

Noxious Stimulation Attenuates Ketamine-induced Neuroapoptosis in the Developing Rat Brain

Abstract: The administration of ketamine with concurrent noxious stimulation results in the attenuation of the neuroapoptotic response. These findings suggest that concurrent surgery and procedural pain attenuates ketamine-induced neuroapoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 40 publications
1
49
0
1
Order By: Relevance
“…Lastly, most experiments that were conducted in newborn rodents were not performed during a surgical stimulation or in the presence of inflammation. Some studies have reported no effect of surgical stimulation on apoptosis in the rodent model [13 • ], whereas others found that it attenuated the response [32]. This issue remains unresolved.…”
Section: Translating Animal Data To Humansmentioning
confidence: 90%
“…Lastly, most experiments that were conducted in newborn rodents were not performed during a surgical stimulation or in the presence of inflammation. Some studies have reported no effect of surgical stimulation on apoptosis in the rodent model [13 • ], whereas others found that it attenuated the response [32]. This issue remains unresolved.…”
Section: Translating Animal Data To Humansmentioning
confidence: 90%
“…Several anesthetics, including ketamine, midazolam, isoflurane, and propofol, have been reported to cause neurodegeneration in the developing brain and subsequent cognitive dysfunction in several animal models [2][3][4][5][6][7]10]. Propofol has also been reported to cause neuroapoptosis in the developing brain at clinically relevant concentrations and durations, leading to neurocognitive dysfunction [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of anesthetics and sedative agents in rodents during synaptogenesis has been shown to have marked degenerative effects [2][3][4][5][6][7] associated with long-term neurocognitive deficits. The present study demonstrates that propofol caused cellular degeneration and led to long-term neuronal deficits in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the results of tests regarding the possible neurotoxic effects of the drugs used for general anaesthesia are inconsistent or inexplicit, great caution is recommended when qualifying the youngest children (www.SmartTots.org) for surgeries/scheduled procedures under general anaesthesia that could be performed at older ages without detriment to the patient's health [21][22][23][24][25][26][27][28].…”
Section: Surgical Planmentioning
confidence: 99%